A Decision Support System For The Selection Of Exemplary Students With AHP Method At SMP IT Generasi Rabbani Of Bengkulu City - Wansa S Junizar; Dewi Suranti; Hendri Alamsyah (Penerbit Jurnal Indonesia, 2022)
To increase the enthusiasm of the students of SMP IT Generasi Rabbani Bengkulu, the school gave awards to exemplary students. By making an assessment of Morals, Academics and Worship. However, to determine the model students of SMP IT Generasi Rabbani Bengkulu, so far, they still use the manual calculation method which takes a lot of time and the risk of calculation errors is large. One method that can be used to solve the problem is the Analytical Hierarchy Process (AHP) method, because the AHP method is able to solve multicriteria problems with the stages of determining the priority of elements, making a pairwise comparison matrix of criteria and sub-criteria, normalizing the matrix, as well as ranking and decision results. This study aims to build a decision support system application for selecting exemplary students using Visual Basic. Net and SQL Server 2008r2 Database at SMP IT Generasi Rabbani Bengkulu therefore it can help the school to determine and select prospective exemplary students quickly and accurately based on predetermined criteria. From the results of functional testing carried out on the application, it is found that some of the functions contained in the application can run well. And the results of the comparison show that there are differences in the value of each student and are able to provide a ranking order of student scores from the highest to the lowest score. Based on the results of research conducted, the AHP method is able to provide convenience in the decision-making process quickly and precisely for the selection of exemplary students therefore the highest score is 0.53 and the lowest value is 0.24.